Neurophysiological Correlates of Featural and Spacing Processing for Face and Non-face Stimuli - Negrini, Marcello; Brkić, Diandra; Pizzamiglio, Sara; Premoli, Isabella; Rivolta, Davide (Frontiers in Psychology, 2017)
The peculiar ability of humans to recognise hundreds of faces at a glance has been attributed to face-specific perceptual mechanisms known as holistic processing. Holistic processing includes the ability to discriminate individual facial features (i.e., featural processing) and their spatial relationships (i.e., spacing processing). Here, we aimed to characterise the spatio-temporal dynamics of featural- and spacing- processing of faces and objects. Nineteen healthy volunteers completed a newly created perceptual discrimination task for faces and objects (i.e., the “University of East London Face Task”) while their brain activity was recorded with a high-density (128 electrodes) electroencephalogram (EEG). Our results showed that early event related potentials (ERPs) at around 100 ms post-stimulus onset (i.e., P100) are sensitive to both facial features and spacing between the features. Spacing and features discriminability for objects occurred at circa 200 ms post-stimulus onset (P200). These findings indicate the existence of neurophysiological correlates of spacing vs. features processing in both face and objects, and demonstrate faster brain processing for faces.